Technology-Enhanced Language Learning in Community-Based Classes for Adult Migrants - Bronagh Catibusic; Shadi Karazi; Jing Deng (Teanga: The Journal of the Irish Association for Applied Linguistics, 2023)
This paper reports on a research project developed in partnership with Fáilte Isteach, an initiative which welcomes migrants and promotes integration through volunteer-led English conversation classes in local communities across Ireland. The research considers the impact of the COVID-19 pandemic on this community-based language support for adult migrants by investigating the experience of online learning in Fáilte Isteach classes. It also explores the potential of technology-enhanced approaches to learning in these informal language classes in the post-pandemic environment. This mixed-methods study involved an initial survey of Fáilte Isteach learners and tutors to understand their perspectives on online learning during the pandemic, followed by a series of training workshops for Fáilte Isteach tutors, in which they could engage with digital tools and create technology-enhanced language learning resources for use with their own classes. Findings from the analysis of the qualitative and quantitative data collected through the survey and the workshop series revealed challenges associated with online learning during the pandemic, particularly regarding access to technology, digital skills, and the lack of social interaction in the online environment. Nevertheless, both learners and tutors identified positive aspects of their online experience and expressed interest in blended approaches as a complement to face-to-face learning. The findings of this research demonstrate the value of training in relation to digital engagement, as evident in the development of technology-enhanced resources through the workshop series. They further indicate how the use of accessible digital tools may benefit adult migrant learners and volunteer tutors in community-based language classes in the post-pandemic context. They also highlight the increasing need for English language support for adult migrants in Ireland and the valuable role of informal volunteer-led classes in local integration.